The Sharing Economy: Definition, Measurement and its Relationship to Capitalism - Andreas Bergh; Alexander Funcke; Joakim Wernberg (Research Institute of Industrial Economics (IFN), 2021)
For the past decade, the sharing economy has not only grown but also expanded to cover a wide variety of different activities across the globe. Despite a lot of research, there is still no agreement on how to define and measure the sharing economy, and no consensus on whether the sharing economy is a part of or an alternative to a regular capitalist economy. This paper contributes by presenting a framework for classification of firms and services in three dimensions (decentralized supply, ad hoc matchmaking and microtransactions), thus effectively creating a definition of the sharing economy. Using clickstream data collected in 2016-2017, we show that the sharing economy consists of many services, but the distribution is highly skewed: Six percent of the services account for 90 percent of the traffic. Using cross-country regressions for 114 countries, we show that while the most important determinant of sharing economy usage is internet access, usage is significantly higher in countries with fewer regulation of capital, labor, and business. We conclude that the sharing enables new types of entrepreneurial efforts within the digitized capitalist economy.
Keywords: O33; P12; O57; M20; 330; Economic freedom; Sharing economy; Broadband; Capitalism